Verbal Representation of Ideas about Motherhood (in Russian Dialects of South of Tyumen Region) - P. E. Bagirova; E. L. Marandina (Научный диалог, 2022)
The results of the speech expression study of ideas about motherhood in Russian dialects of the south of the Tyumen region are systematized. Dialect materials are accompanied by linguistic and cultural commentary, taking into account the contextual use of vocabulary. As a result of the interpretation of verbal markers of motherhood, a range of situations that acquire a linguistic assessment in rural discourse (names denoting the state of pregnancy, childbirth and child care, nominations of an illegitimate and adopted child, aspects of education) are revealed, the nature of lexical and phraseological units chosen by informants for designations of certain concepts (dialect / all-Russian, evaluative / neutral, etc.). Concepts of motherhood are implemented in a rich and detailed vocabulary, characterized by a plurality of names for the same realities, differing in the ways of semantic identification. Most of the nominations are characterized by a transparent internal form, which makes it possible to actualize the prevailing value attitudes and stereotypes in the word.